Association between living habits, indoor humidity, ventilation and asthma among residents in the tropical regions of China - Chen, Mingming; Zhang, Kun; Zhang, Xin; Gao, Jun; Zhang, Rongguang; Wei, Xiaoli; Cao, Wenting (Frontiers in Public Health, 2023)
Objective Asthma is a major public health problem that affects both children and adults, and its prevalence varies among people with different climatic characteristics and living habits. However, few studies have investigated the prevalence and risk factors for asthma among tropical residents in China. Therefore, this study aims to investigate the correlation between individuals’ living environment and daily habits in Hainan Province, and the occurrence of asthma. Methods This cross-sectional study collected data from 1021 participants in three regions of the Hainan Province. A questionnaire derived from the European Community Respiratory Health Survey was used to collect data on demographics, living habits, self-reported asthma, and respiratory system-related symptoms. Logistic regression was used for univariate and multivariate analyses to screen for relative risk factors associated with asthma. Results Among the 1,021 subjects investigated, the prevalence rate of self-reported asthma was 18.6%. Significant risk factors for asthma include hair dyeing, longer living time in Hainan, higher BMI, and living in a damp and musty room. Protective factors included fruit intake, years of higher education, and indoor timing of natural ventilation. Conclusion Higher frequency of hair dyeing, higher body mass index (BMI), longer living in Hainan, lower frequency of fruit intake, fewer years of education, a damp and musty room, and no indoor timing natural ventilation were associated with an increased risk of asthma.